Textile/Al2O3–TiO2 nanocomposite as an antimicrobial and radical scavenger wound dressing. Issue 10 (20th January 2016) - Parham, Shokoh; Chandren, Sheela; Wicaksono, Dedy H. B.; Bagherbaigi, Saeedeh; Lee, Siew Ling; Yuan, Lai Sin; Nur, Hadi
Abstract : Improving the antimicrobial activity and radical scavenging ability of a textile-based nanocomposite is the key issue in developing a good and flexible wound dressing. Abstract : Improving the antimicrobial activity and radical scavenging ability of a textile-based nanocomposite (textile/TiO2, textile/Al2 O3 /TiO2, textile/Al2 O3 and textile/Al2 O3 –TiO2 bimetal oxide nanocomposite) is the key issue in developing a good and flexible wound dressing. In this work, flexible textile attached with Al2 O3 –TiO2 nanoparticles was prepared by dipping the textile in a suspension containing Al2 O3 –TiO2 nanoparticles (150 mmol l −1 ). The mean radical scavenging ability for textile/TiO2, textile/Al2 O3 /TiO2, textile/Al2 O3 and textile/Al2 O3 –TiO2 bimetal oxide nanocomposites as measured by liquid ultraviolet visible spectroscopy (UV-Vis) coupled with dependence formula was 0.2%, 35.5%, 35.0% and 38.2%, respectively. Based on the X-ray diffraction (XRD) patterns, the preface reactive oxygen species (ROS) scavenging ability shown by the textile/Al2 O3 –TiO2 bimetal oxide nanocomposite is most probably caused by the crystal structure concluding in a corundum-like structure, with Al 3+ ions filling the octahedral sites in the lattice. Increased antimicrobial activity measured by optical density at 600 nm recorded for textile/Al2 O3 –TiO2 bimetal oxide nanocomposites showed better interaction between Al2 O3 and TiO2 nanoparticles. This good interaction is expected to lead to better antimicrobial and radical scavenging ability as shown by the E. coli and human skin fibroblast (HSF) cytotoxicity tests, respectively.